Endogenous timing and the choice of quality in a vertically differentiated duopoly - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1997)
The endogenous choice of timing is discussed in a vertically differentiated duopoly where quality improvement requires a fixed convex cost. The timing decision concerns the quality stage. Using an extended game with observable delay, it is shown that only simultaneous equilibria can arise. This puts into question the ability of Stackelberg games to describe the entry process.
Keywords: 330